The Swedish version of the TeamSTEPPS® teamwork attitudes questionnaire (T-TAQ): A validation study - Marie Louise Hall-Lord; Carina Bååth; Randi Ballangrud; Anna Nordin (BMC, 2021)
Abstract Background Effective teamwork is essential for delivering safe health care. It is important to increase patient safety in healthcare by conducting interprofessional team training with both healthcare professionals and undergraduate students. Validated questionnaires that evaluate team training activities contribute to valuable knowledge regarding changes in attitudes toward teamwork. The aim of the study was to test the reliability and structural validity of the Swedish version of the TeamSTEPPS® Teamwork Attitudes Questionnaire (T-TAQ). Methods The study had a cross-sectional design. Four hospitals in three health care regions in Sweden participated in the study. In total, 458 healthcare professionals, response rate 39.4%, completed the questionnaire. The T-TAQ, which consists of 30 items and covers five dimensions (Team Structure, Leadership, Situation Monitoring, Mutual Support and Communication), was translated to Swedish. A paper version of the T-TAQ was distributed to healthcare professionals (physicians, registered nurses, midwives, nursing assistants and allied health professionals) from the hospitals. Reliability and validity were tested using Cronbach's alpha and confirmatory factor analysis. Results Cronbach's alpha was 0.70 for the total T-TAQ and ranged from 0.41 to 0.87 for the individual dimensions. The goodness-of-fit indexes in the confirmatory factor analysis (Model 2) revealed a normed chi-square of 2.96, a root mean square error of approximation of 0.068, a Tucker-Lewis index of 0.785 and a comparative fit index of 0.808. Conclusions The Swedish version of the T-TAQ has some potential to measure healthcare professionals' general attitudes toward the core components of teamwork in hospital settings. Further validation studies of the Swedish version of the T-TAQ are required, with samples representing both healthcare professionals and students from various healthcare disciplines and educational levels.